Gabapentinoid Abuse in France: Evidence on Health Consequences and New Points of Vigilance - Tambon, Marine; Ponté, Camille; Jouanjus, Emilie; Fouilhé, Nathalie; Micallef, Joelle; Lapeyre-Mestre, Maryse; , the French Addictovigilance Network (FAN) (Frontiers in Psychiatry, 2021)
Introduction Gabapentinoid drugs (gabapentin and pregabalin) are widely used worldwide for epileptic and pain disorders. First signals of gabapentinoid abuse occurred in the last decade. This study aims to describe clinical characteristics of gabapentinoid use related disorders and health consequences in France. Materials and methods. We designed a multisource investigation reviewing data reported to the French Addictovigilance Network (FAN) with pregabalin and gabapentin from 2010 to 2019. Information was obtained through the analysis of Spontaneous Reports (SRs) notified by health professionals and the pharmacoepidemiological surveys OSIAP (suspicious prescriptions forms indicators of potential abuse), OPPIDUM (observation of illicit drugs and misuse of psychotropic medications), DRAMES (death related to prescription drugs and other substances) and DTA (toxic deaths due to analgesics). Results Over 2010-2019 period, were collected: i) 265 SRs (258 pregabalin; 7 gabapentin); ii) 816 forged prescription forms (805 pregabalin, 10 gabapentin, 1 involving both drugs); iii) 145 cases of gabapentinoid use in people who use drugs (121 pregabalin; 24 gabapentin) and iv) 31 cases of gabapentinoid-related deaths (25 pregabalin; 6 gabapentin). Risk factors of gabapentinoid abuse were opioid use disorders or psychiatric history, but cases of primary abuse in subjects without any substance abuse history were observed. Adverse outcomes concern almost exclusively pregabalin, with coma, dyspnea, convulsion, and conduction disorders. Treatment demands increased from 10.6% in 2018 to 23.1% in 2019, with pregabalin cited as the first substance leading to addictological care in the 2019 OPPIDUM survey. Gabapentinoid-related deaths increased over time. Pregabalin has become the first drug mentioned in forged prescriptions in 2019 (23.8% of OSIAP), while it ranked at the 15th position in 2017 (2.6%). Discussion This study shows the importance of addictovigilance monitoring for gabapentinoids. Addictovigilance data helped to make visible the gabapentinoid-abuse related health harms (hospitalization for serious neurologic, psychiatric or cardiac effects, requests for addictological support and deaths) and to confirm the intrinsic abuse potential of pregabalin. These data highlight new points of vigilance considering observed primary abuse. At this point in France, the risk of abuse and related complications is very apparent with pregabalin. Still, it is identical to that observed elsewhere with gabapentin.